Supplemental Fiber Affects Body Temperature and Fecal Metabolites but Not Respiratory Rate or Body Composition in Mid-Distance Training Sled Dogs - Thornton, Emma; Robinson, Eve; Templeman, James R.; Bruggink, Lindy; Bower, Michael; Cant, John P.; Holloway, Graham P.; Swanson, Kelly S.; Squires, E. James; Shoveller, Anna K. (Frontiers in Veterinary Science, 2021)
Dietary fiber effects canine physiology in many ways, such as increasing colonic absorption of water and improving gut health, both of which may positively impact exercise performance. The objectives of this study were to investigate the effects of increased dietary soluble fiber and incremental training on respiratory rate (RR), internal body temperature (BT), body composition, and fecal metabolites in mid-distance training sled dogs. Fourteen dogs (12 Siberian and 2 Alaskan huskies) were blocked by age, sex, and BW, then randomly allocated into one of two diet groups. Seven dogs were fed a dry extruded control diet (Ctl) with an insoluble: soluble fiber ratio of 4:1 (0.74% soluble fiber on a dry matter basis), and seven dogs were fed a dry extruded treatment diet (Trt) with an insoluble: soluble fiber ratio of 3:1 (2.12% soluble fiber on a dry matter basis). Fecal samples were taken once a week. All dogs underwent 9 weeks of incremental exercise conditioning where the running distance was designed to increase each week. Every three weeks, external telemetry equipment was used to non-invasively measure and record RR and internal BT at a resting, working, and post-exercise recovery state. Body composition was measured on weeks -1 and 9 using quantitative magnetic resonance. Body composition, RR, BT and fecal metabolites were analyzed using a mixed model with dog as a random effect and week and diet group as fixed effects. Dogs on Trt had lower working and post-exercise BT compared to Ctl (P < 0.05). In addition, Trt dogs had lower recovery BT at week 2 and 5 compared to Ctl dogs (P < 0.05). Treatment dogs had greater fecal short-chain fatty acid concentrations compared to Ctl (P < 0.05). Diet had no effect on RR or body composition (P > 0.10), but exercise resulted in an overall 7% increase in lean and 3.5% decrease in fat mass (P < 0.05). These data suggest that increasing dietary soluble fiber may positively influence BT and gut health; however, has no effect on RR or body composition.